Gender in Music Production - Hepworth-Sawyer, Russ (Focal Press, 2020)
The field of music production has for many years been regarded as male-dominated. Despite growing acknowledgement of this fact, and some evidence of diversification, it is clear that gender representation on the whole remains quite unbalanced. Gender in Music Production brings together industry leaders, practitioners, and academics to present and analyze the situation of gender within the wider context of music production as well as to propose potential directions for the future of the field. This much-anticipated volume explores a wide range of topics, covering historical and contextual perspectives on women in the industry, interviews, case studies, individual position pieces, as well as informed analysis of current challenges and opportunities for change. Ground-breaking in its synthesis of perspectives, Gender in Music Production offers a broadly considered and thought-provoking resource for professionals, students, and researchers working in the field of music production today.
Title from content provider
Keywords: Sex discrimination against women; Women in the music trade; Women musicians; Women sound recording executives and producers; Discrimination à l'égard des femmes; Femmes dans l'industrie musicale; Musiciennes; Productrices d'enregistrements sonores; musicians